Spatial Confinement Effects of Microcapsule Catalyst for Improved Coking‐ and Sintering‐Resistant Behaviors Toward CO2 Reforming of Methane Reaction. Issue 4 (25th March 2019) - Han, Bing; Amoo, Cederick Cyril; Zhang, Guihua; Cheng, Shilin; Mazonde, Brighton; Javed, Mudassar; Gai, Xikun; Lu, Chengxue; Yang, Ruiqin; Xing, Chuang
Abstract : The CO2 dry reforming of methane (DRM) reaction is an important technology with high prospects to reduce greenhouse gas emissions while simultaneously producing syngas for industrial usage. To date, the lack of an effective catalyst for the reaction has inhibited its commercialization. The coking and sintering behaviors of the catalysts are key factors for commercial production of syngas from DRM reaction. A microcapsule catalyst prepared by sol–gel method with Ni/ZSM‐5 as core and amorphous SiO2 as shell is successfully synthesized. The characterizations of the catalysts are analyzed using X‐ray powder diffraction (XRD), transmission electron microscopy (TEM), H2 temperature programmed reduction (H2 ‐TPR), NH3 temperature programmed desorption (NH3 ‐TPD), and thermogravimetry & differential scanning calorimetry (TGA‐DSC). The spatial confinement of the Ni metal particles between the SiO2 shell and ZSM‐5 suppresses Ni particles aggregation by strengthening the interaction between Ni particles and ZSM‐5 core. The coking‐resistant ability is equally improved. The capsule catalysts isolate the contact between the carbon deposits and the nickel active centre, thus improving the activity of the catalysts. 10Ni/ZSM‐5@SiO2 emerged superior in activity in comparison to other catalysts. Abstract : Sintering and coking of catalysts remain major challenges inhibiting commercialization of the dry reforming of methane (DRM) reaction. These challenges have been successfully minimized by the fabrication of an amorphous SiO2 shell on Ni/ZSM‐5 catalysts. Great improvement in anticoking‐ and sintering‐resistant ability is observed for coated catalysts over corresponding uncoated ones.